Optimasi Skema Gaji Karyawan UKM XYZ Di Kota Bogor Menggunakan Metode Adhered Dan Overlapping - Welvinanda, Adzahrra; Cendikia Succesy, Betah; Jinan Lam’a, Fairuz; Puspitasari, Intan; Fairuzi, Sabilatussilmi; Kartika, Lindawati (BULLET : Jurnal Multidisiplin Ilmu, 2024)
UKM XYZ is one of the culinary businesses located in Bogor City, West Java, which has been established since 1963. Managed by 23 staff members with various roles, ranging from Supervisors to security guards, the welfare of employees is crucial in the business. One aspect of employee welfare can be observed through the compensation system implemented. Compensation provided may include basic salary, allowances, and other benefits. UKM XYZ adopts a daily wage payment system for its staff, with the amount varying based on the job type within the UKM. However, the current compensation system lacks consideration for other factors, making it less than ideal. Therefore, this research aims to evaluate the compensation system for UKM XYZ. Drawing on Salary mapping theory, this study seeks to provide a better understanding of the compensation system for the UKM. The methods employed in this research include compensable factors, analysis of the given system (job grading), and a simple method with adhered and overlapping schemes, aimed at enhancing employee satisfaction within the compensation system.